Seeking Comfort from Online Strangers: An Analysis of ‘Kind Words 2' Gameplay - Sandra, Ni Putu Anindhitha Ayesha (ULTIMART Jurnal Komunikasi Visual, 2025)
In an era where digital communication often lacks emotional resonance, the video game ‘Kind Words 2’ emerges as a distinctive platform for anonymous, empathetic exchange. This study investigates how anonymous interactions within the game promote emotional support, comfort, and a sense of companionship among players. Employing a mixed-methods approach—including self-observation, online surveys, and semi-structured interviews—the research uncovers key findings: players consistently report feelings of emotional relief, validation, and reduced loneliness after engaging with the community. The study also reveals that anonymity significantly enhances openness and authenticity in communication, allowing players to share vulnerabilities without fear of judgment. These findings demonstrate the game's potential as a digital tool for fostering mental well-being and community resilience. By highlighting how anonymous digital environments can facilitate meaningful social support, this research contributes to ongoing discussions on the therapeutic potential of video games and their role in addressing emotional needs in online spaces.  Keywords: ‘kind words 2’; anonymous social support; empathy-driven; game design; online community interaction; emotional expression in games